Combining Cognitive Maps and MCDA Techniques to Assist in Estimating Residential Housing Values - Ferreira, F.; Spahr, R.; Sunderman, M. (2015 BAI International Conference, 2015)
Much has been written about the appraisal process and the process that is, or should be, employed in the establishment of initial offering prices on residential real estate. However, imputation of initial offer prices as estimates of actual market prices for residential real estate is a complex undertaking. Residential real estate fundamental values deviate due to a variety of factors that must be considered in the evaluation process. We conduct a panel study using a multiple criteria decision analysis (MCDA) framework that utilizes the skills and knowledge of a panel of residential real estate experts (i.e. appraisers and realtors). We demonstrate how the integrated use of cognitive maps and measuring attractiveness by a categorical based evaluation technique (MACBETH) may assist in estimating appropriate offer/sale prices and strengthening current valuation approaches such as using comparables and/or hedonic modeling. The strengths and weaknesses of our multiple criteria framework are also discussed.